Campagne de la Calypso au large des côtes Atlantiques de l'Amérique du Sud I. 33. Annélides Polychètes. - Rullier, Francois; Amoureux, Louis (Annales de l'Institut océanographique, (Nouv. Ser.), 1979)
More than 1,700 polychaetes are analysed. They were dredged or trawled along the coasts of Brazil, Uruguay and Argentina, at depths of between 0 and 750 m, from 16 November 1961 to 9 January 1962. About 175 species have been listed: a list with systematic and ecological notes is given for each species. Some of these are the first record in these areas. Four species are new to science and have been described: Euphrosyne uruguyaensis, Nuchalosyllis lamellicornis, Neopseudocapitella brasiliensis, Neovermilia aberrans . Two sub-species are also new: Lepidonotus laevis brasiliensis [Sic. In the text body it's Lepidonotus brasiliensis subspecies laevis], Pholoe minuta hirsuta . This paper ends with 130 bibliographical references.
World Polychaeta Database (WPolyDb). Not known to be available online, except here. OCR may be poor in the file